ANALISIS PENERAPAN PEMBELAJARAN MATEMATIKA BERBASIS PMRI PADA SEKOLAH DASAR DI KOTA BANDUNG - Masta Hutajulu; Marchasan Lexbin E.J.R (IKIP Siliwangi Bandung, 2016)
The research is conducted to observe if Mathematics teacher who use PMRI base consistently apply the characteristic especially to students of grade 4 primary. The purpose of this research is to give contribution to all Mathematics teachers who apply PMRI. The data collection technique that use is observation method. The results of research are: 1) the application of PMRI in collaborator school (grade 4 primary) is consistent to the characteristics of PMRI. 2) Mathematics teachers who apply PMRI use the method according to the standard.Keyword: Realistic Mathematics Education of Indonesia (PMRI)